Functional Outcome of Osteosynthesis with PHILOS in Elderly Patients: Experience at Tertiary Care Centre - Narendra Singh Kushwaha; Sushil Kumar Saini; Ashutosh Verma; Ravindra Mohan; Atul Kumar Saroj; Arpit Singh; M. C. Prajwal (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Increased risk of proximal humerus fractures are seen in elderly group as their bones are osteoporotic or brittle. Mode of trauma in elderly patients with severe osteoporosis, fractures usually resulted from low velocity indirect trauma while high velocity trauma like road traffic accident was the cause of these fractures in younger age group. Surgery can be an option to obtain a better functional outcome or when a complex fracture needs to be fixed. With the advantages and the paucity of data on the functional outcome and efficacy of the following internal fixation with the PHILOS plate for displaced proximal humerus fractures in mind, the present study was planned. Methodology: Patients who fulfilled the selection criteria were informed about the study and were then enrolled. Following the surgery, patients were followed up regularly at six weeks, three months, and six months. Final outcome was analyzed by Constant Shoulder Score. Christopher Constant, with the help of the late Alan Murley during the years 1981–1986, devised the Constant Score, which was first presented in a university thesis in 1986 and whose methodology was later published in 1987. Results: A total of 30 patients sustained with proximal humerus fractures were studied. In this study of final assessment were Found 73.2 % good to excellent outcome by using the Constant Shoulder Score. Conclusion: Following this study, the inference can be drawn that proximal humerus internal locking system for the management of proximal humerus fractures give a good functional outcome in most patients. Hence PHILOS plate application for fixation of fracture proximal humerus in elderly patients hence allowing early mobilization of the shoulder.